Proposed Amendment on the Reform of the IMF Executive Board and Fourteenth General Review of Quotas : Status of Acceptances and Consents. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This status report reviews progress toward implementation of the 2010 Governance and Quota Reforms. It updates the status of consents to the proposed quota increases under the 14th General Review of Quotas and of acceptances of the Proposed Seventh Amendment on the Reform of the Executive Board ('Board Reform Amendment' or 'Seventh Amendment') as set out in the Board of Governors Resolution No. 66-2.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; Quota Increase; Quota Reform; Reform Of The Executive Board; Report Reviews Progress; Central African Republic